Methodology for planning water supply under drought conditions - Tsiourtis N.X. (Drought management: scientific and technological innovations, 2008)
The water supply scenarios under water supply shortage caused by droughts, so that the adverse effects are minimized is the subject of discussion in this paper. This paper outlines a methodology which enables the estimation of the probability of satisfaction of a scenario of water supply using the original storage and the probability of having the necessary inflow so that the total volume of the inflow plus the existing storage minus the evaporation and losses equal or exceed the water demand of the scenario in consideration. The probabilities of inflows being equal or exceeded are derived from the actual long-term inflows for certain period. Using the water supply scenarios for full or part satisfaction of the normal water demand and carrying out a mass water balance the required inflow is calculated. For each Scenario the required inflow is calculated and for this inflow the probability of occurrence of this inflow been equalled or exceeded is derived from the normal distribution function. For each scenario an array of probabilities as a function of starting time (starting early in the beginning of the Hydrological Year and ending next April), is derived, showing the probability of satisfaction of the demand. From these curves the water managers will be able to select the most probable scenario that may be adopted to minimize or eliminate the water cuts in the water supply scenarios. The derived water supply scenarios will span over a period of twelve months providing to the water consumers the reliability and security of water supply.
1. International Conference Drought Management: Scientific and Technological Innovations, 2008/06/12-14, Zaragoza (Spain)